2009
DOI: 10.1183/09031936.00195708
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-retinoic acid inhibits tumour growth of malignant pleural mesothelioma in mice

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive malignant tumour of mesothelial origin associated with asbestos exposure. Because MPM has limited response to conventional chemotherapy and radiotherapy, the prognosis is very poor. Several researchers have reported that cytokines such as interleukin (IL)-6 play an important role in the growth of MPM. Previously, it was reported that all-trans-retinoic acid (ATRA) inhibited the production and function of IL-6 and transforming growth factor (TGF)-b1 in exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Fibroblast migration plays an important role in pulmonary fibrosis, and a recent report showed that Ang-1 induced endothelial cell migration [31]. On the other hand, we found that Ang-1 induced malignant pleural mesothelioma cell migration, which has a mesenchymal origin similar to lung fibroblasts [21]. Therefore, we examined whether Calpeptin had an effect on Ang-1/Tie2 expression and Ang-1-dependent migration of lung fibroblasts and showed that Calpeptin decreased both the Ang-1 and Tie-2 mRNA expression of cultured lung fibroblasts as well as the Ang-1-induced migration of these cells.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Fibroblast migration plays an important role in pulmonary fibrosis, and a recent report showed that Ang-1 induced endothelial cell migration [31]. On the other hand, we found that Ang-1 induced malignant pleural mesothelioma cell migration, which has a mesenchymal origin similar to lung fibroblasts [21]. Therefore, we examined whether Calpeptin had an effect on Ang-1/Tie2 expression and Ang-1-dependent migration of lung fibroblasts and showed that Calpeptin decreased both the Ang-1 and Tie-2 mRNA expression of cultured lung fibroblasts as well as the Ang-1-induced migration of these cells.…”
Section: Discussionmentioning
confidence: 46%
“…Quantitative real-time RT-PCR was performed using TaqMan Gene expression products as described previously [17][18][19]21]. The levels of mRNA are represented as the ratio to 18SrRNA (Applied Biosystems), an endogenous control.…”
Section: Quantitative Real-time Reverse Transcription-polymerase Chaimentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative, real-time RT-PCR was performed as previously described [10][11][12] using TaqMan Gene expression products for human Tie-2, Ang-1 and Ang-2. 18S ribosomal RNA served as an endogenous control (Applied Biosystems).…”
Section: Cell Culturementioning
confidence: 99%
“…The cell proliferation assay was performed as previously described [9,10,12]. The MPM cell lines and MeT-5A cells were cultured in 96-well flat-bottomed culture plates for 2 days with or without recombinant human Ang-1 (1-100 ng?mL -1 ).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%